IEEE International Symposium on High-Performance Comp Architecture 2012
DOI: 10.1109/hpca.2012.6169044
|View full text |Cite
|
Sign up to set email alerts
|

Accelerating business analytics applications

Abstract: Business text analytics applications have seen rapid growth, driven by the mining of data for various decision making processes. Regular expression processing is an important component of these applications, consuming as much as 50% of their total execution time. While prior work on accelerating regular expression processing has focused on Network Intrusion Detection Systems, business analytics applications impose different requirements on regular expression processing efficiency. We present an analytical mode… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
14
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(14 citation statements)
references
References 32 publications
0
14
0
Order By: Relevance
“…The available operations treat the data as vectors and focus largely on arithmetic and shuffling operations on the vector values. Many programmers have retrofitted and vectorized other types of programs, notably text parsing [5,32] and regular expression matching [45] and database kernels [55,18,31]. Our experiments in Section 2.2 using a state of the art SIMD range partitioning [46] indicate that vector-based traversal improves throughput somewhat but fails to fully saturate DRAM bandwidth.…”
Section: Related Workmentioning
confidence: 97%
See 1 more Smart Citation
“…The available operations treat the data as vectors and focus largely on arithmetic and shuffling operations on the vector values. Many programmers have retrofitted and vectorized other types of programs, notably text parsing [5,32] and regular expression matching [45] and database kernels [55,18,31]. Our experiments in Section 2.2 using a state of the art SIMD range partitioning [46] indicate that vector-based traversal improves throughput somewhat but fails to fully saturate DRAM bandwidth.…”
Section: Related Workmentioning
confidence: 97%
“…One recent study of regular expression matching compared different strategies for acceleration [45]. The study concluded that SIMD software was the best option, due to the fast data and control transfers between the scalar CPU and the vector unit.…”
Section: Related Workmentioning
confidence: 99%
“…GPUs are perhaps the most visible and among the most successful such processors targeting graphics applications [5,30]. There is a large body of research around other domain-specific acceleration: Convolution Engine [32] targets image processing kernels and stencil computations, [33] uses specialization to speed up regular expression matching in queries, and [18] accelerates H.264 video encoders. In spirit these projects share similarities with the Q100, but in their design and target particulars they are quite different.…”
Section: Related Workmentioning
confidence: 99%
“…The available operations treat the data as vectors and focus largely on arithmetic and shuffling operations on the vector values. Many programmers have retrofitted and vectorized other types of programs, notably text parsing [Cameron and Lin 2009;Lin et al 2012] and regular expression matching [Salapura et al 2012] and database kernels [Zhou and Ross 2002;Govindaraju and Manocha 2005;Krueger et al 2011]. Our experiments in Section 3 using a state-of-the-art SIMD range partitioning [Polychroniou and Ross 2014] indicate that vector-based traversal improves throughput and energy markedly.…”
Section: Related Workmentioning
confidence: 99%
“…One recent study of regular expression matching compared different strategies for acceleration [Salapura et al 2012]. The study concluded that SIMD software was the best option due to the fast data and control transfers between the scalar CPU and the vector unit.…”
Section: Related Workmentioning
confidence: 99%